β-Blockers and benzodiazepines location in SDS and bile salt micellar systems - Reis, Salette (2019)
The work here described aimed to find out the location of the different species of two families of pharmaceutical substances, namely two beta-blockers (atenolol and nadolol) and two benzodiazepines (midazolam and nitrazepam) in synthetic (sodium dodecyl sulphate, SDS) and natural (bile salts-sodium cholate and sodium deoxycholate) micellar aggregate solutions. Electronic spin resonance spectroscopy studies were carried out, at 25 degrees C and at an ionic strength of 0.10 M in NaCl, using 5-, 12- and 16-doxylstearic acid probes (AS). The immobilization degree of solubilized stearic acid spin probes was found to vary with the position of the nitroxide group in the sequence 5-doxylstearic acid>12-doxylstearic acid>16-doxylstearic acid for SDS and 12-doxylstearic acid>5-doxylstearic acid>16-doxylstearic acid for both bile salts investigated. Therefore, from the rotational correlational time values obtained, it can be inferred that the structure of bile salt micelles is markedly different from that of SDS micelles and the results suggest that the bile salt micelles studied have similar structure independently of differences in the molecular structure of the respective bile salts. Drug location studies were performed at pH 4.0 (SDS solutions) or 7.0 (bile salt solutions) and 10.8 in order to study the effect of the drug ionisation on its relative position on micelles. The results have shown that drug location is controlled by the (i) drug hydrophilicity and acid/base properties, with the more soluble compound in water (atenolol) exhibiting smaller variation of rotational correlational time (in SDS and bile salts solutions), and with both beta-blockers exhibiting smaller deviations in the protonated forms and (ii) the bile salt monomers, with the dihydroxylic bile salt (deoxycholate) producing larger differences. The work described herein allow us to conclude that the (protonated) beta-blockers are probably located on the surface of the detergent micelles, and linked to them by means of essentially electrostatic forces, while the (neutral) benzodiazepines are probably located deeper in the interior of the micelles.